Innovative approaches for learning: Strengthening numeracy literacy with creative problem solving - Adlina, Nadiyah; Susanti, Ely (Jurnal Gantang, 2026)
Numeracy literacy is one of the essential skills students must possess to use numbers and mathematical symbols to solve everyday problems, present information in various forms such as tables, graphs, or charts, and interpret analysis results as a basis for decision-making. However, students' numeracy literacy skills still need to be strengthened through the application of innovative, problem-solving-centered learning models. Therefore, this study aims to describe students' numeracy skills by applying the Creative Problem Solving (CPS) model to the topic of Systems of Linear Equations with Two Variables (SLETV). This study employed a descriptive method involving 33 ninth-grade students. Learning activities were designed by integrating the CPS model's stages into the SLETV problem-solving process. Data was collected through a test developed based on numeracy literacy indicators, then analyzed and categorized into five categories: very good, good, sufficient, insufficient, and very insufficient. The results indicate that the CPS model positively impacts students' numeracy literacy skills, particularly in representing, interpreting, and applying mathematical information in real-life contexts. Based on these findings, this study recommends using innovative approaches, such as CPS, in mathematics instruction to strengthen students' numeracy skills when studying the System of Linear Equations with Two Variables.